2023
DOI: 10.1039/d2dt03770j
|View full text |Cite
|
Sign up to set email alerts
|

Beyond phosphorus: synthesis, reactivity, coordination behaviour and catalytic properties of 1,1′-bis(diphenylstibino)ferrocene

Abstract: Compared to their widely studied phosphine counterparts, ferrocene stibines have received only marginal attention thus far. This paper describes the synthesis of 1,1ʹ-bis(diphenylstibino)ferrocene (1*), which is an antimony analogue of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 130 publications
(73 reference statements)
2
13
0
Order By: Relevance
“…The structure of 1 ·BH 3 comprises a regular ferrocene unit with parallel cyclopentadienyl rings (dihedral angle 1.5(2)°) and substituents in approximately anti positions (the torsion angle τ = C1–Cg1–Cg2–C6, where Cg1 and Cg2 denote the centroids of the cyclopentadienyl rings C(1–5) and C(6–10), respectively, is 160.3(2)°; see Figure S17). The arrangement of the stibine substituent was similar to that in G or 1-(diphenylstibino)-2-vinylferrocene, i.e., with Sb–C­(Ph) distances slightly longer than the Sb–C­(ferrocenyl) bond and with C­(Ph)–Sb–C­(Ph) angles wider than the C­(ferrocenyl)–Sb–C­(Ph) angles. In turn, the geometry of the phosphine part compared well with that in dppf·2BH 3 or 1-(diphenylphosphino)-1-methylferrocene–borane (1:1) …”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…The structure of 1 ·BH 3 comprises a regular ferrocene unit with parallel cyclopentadienyl rings (dihedral angle 1.5(2)°) and substituents in approximately anti positions (the torsion angle τ = C1–Cg1–Cg2–C6, where Cg1 and Cg2 denote the centroids of the cyclopentadienyl rings C(1–5) and C(6–10), respectively, is 160.3(2)°; see Figure S17). The arrangement of the stibine substituent was similar to that in G or 1-(diphenylstibino)-2-vinylferrocene, i.e., with Sb–C­(Ph) distances slightly longer than the Sb–C­(ferrocenyl) bond and with C­(Ph)–Sb–C­(Ph) angles wider than the C­(ferrocenyl)–Sb–C­(Ph) angles. In turn, the geometry of the phosphine part compared well with that in dppf·2BH 3 or 1-(diphenylphosphino)-1-methylferrocene–borane (1:1) …”
Section: Resultsmentioning
confidence: 69%
“…The oxidation changed the geometry at the antimony atom from ψ-tetrahedral to trigonal bipyramidal and shortened the Sb–C bonds (cf. the structures of G and the corresponding bis­(stiborane), [Fe­(η 5 -C 5 H 4 SbPh 2 Cl 2 ) 2 ]) . The τ 5 parameter for the stiborane moiety in 12 was 0.86, reflecting that although the Cl–Sb–Cl (axial) angle was close to the ideal 180°, the C–Sb–C angles varied (∼115–128°) for steric reasons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…90 CV of 1,1′-bis(stannyl)ferrocenes Fc(Sn IV Me 3− n Cl n ) 2 ( n = 0, 1, 2) ( 36 ) and Fc(Sn II R) 2 (R = 4- t -Bu-2,6-{P(O)(Oi-Pr) 2 } 2 C 6 H 2 ) ( 37 ) show reversible one-electron oxidations, 91,92 as does 1,1′-bis(diphenylstibino)ferrocene. 93 Polarographic measurements of the [1.1]stannylferrocenophane (( n -Bu) 2 SnFc) 2 ( 38 ) shows two reversible one-electron oxidation waves. 94 Oxidation potentials have also been obtained by CV for ferrocenyl lead compounds Ph 3 PbFc ( 39a ), (Ph 3 Pb) 2 Fc ( 39b ), Ph 2 PbFc 2 ( 40a ) and (Ph 3 Pb)Fc(Ph 2 Pb)Fc ( 40b ) and lead [1.1]ferrocenophane (Ph 2 PbFc) 2 ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Being an essential component in organometallic polymers, [3][4][5][6][7][8][9][10] redox-tunable substances, 6,[11][12][13] organometallic drugs, 14,15 and functional materials, 9,[16][17][18][19][20] ferrocene has played a vital role in homogenous catalysis. [21][22][23][24][25] The principle reasons for its popularity in homogenous catalysis lie in the easy syntheses of its P-functionalized derivatives (such as dppf ) and a flexible backbone, 26,27 which provides an opportunity to stabilize various metal centers by attaining facile geometric changes. 21,28 When such ferrocene-based ligands were further explored in respect to catalysis, it was found that bite angles (β n ) of such ligands, which have a positive effect on the efficiency of catalysts, 29,30 are significantly higher than those found for usual bisphosphanyl ligands (such as dppe), [29][30][31] and can further be manipulated by changing the substituents on phosphorus.…”
Section: Introductionmentioning
confidence: 99%